Anatomy and Physiology of Metabotropic Glutamate Receptors in Mammalian and Avian Auditory System - Tang, Zheng-Quan (HSOA Trends Anat Physiol, 2018)
Glutamate, as the major excitatory neurotransmitter used in the vertebrate brain, activates ionotropic and metabotropic glutamate receptors (iGluRs and mGluRs), which mediate fast and slow neuronal actions, respectively. mGluRs play important modulatory roles in many brain areas, forming potential targets for drugs developed to treat brain disorders. Here, we review studies on mGluRs in the mammalian and avian auditory system. Although anatomical expression of mGluRs in the cochlear nucleus has been well characterized, data for other auditory nuclei await more systematic investigations especially at the electron microscopy level. The physiology of mGluRs has been extensively studied using in vitro brain slice preparations, with a focus on the auditory circuitry in the brainstem. These in vitro physiological studies have demonstrated that mGluRs participate in synaptic transmission, regulate ionic homeostasis, induce synaptic plasticity, and maintain the balance between Excitation and Inhibition (E/I) in a variety of auditory structures. However, the modulatory roles of mGluRs in auditory processing remain largely unclear at the system and behavioral levels, and the functions of mGluRs in auditory disorders remain entirely unknown.